A review of whole brain radiotherapy outcomes in a high epidermal growth factor receptor mutation rate population: Does QUARTZ apply in Asia?. Issue 6 (2nd July 2019) - Ng, Ivy Weishan; Tey, Jeremy Chee Seong; Chia, David Wei Tsau; Yee, Choon Meng; Cheo, Timothy Song Tao
Abstract: Aim: Whole brain radiotherapy (WBRT) is commonly used to treat brain metastases (BM) from nonsmall cell lung cancer (NSCLC). Its utility is increasingly being questioned after a recent randomized trial (QUARTZ) showed that its omission did not significantly impact the survival or quality of life of their patients recruited from UK and Australian centers. We report the patient characteristics and survival outcomes of our local population in comparison with theirs. Methods: Medical records of patients who received WBRT in two tertiary hospitals over 18 months were reviewed. Characteristics and survival outcomes of patient with NSCLC receiving WBRT for the first time were evaluated. Patients with prior excision of BM or stereotactic radiotherapy were excluded. Treatment details including radiotherapy dose and use of tyrosine kinase inhibitors (TKIs) were recorded. Results: Between January 2015 and June 2016, 116 patients with NSCLC received WBRT for their BM. Their median age was 65 years (range, 36‐85) and median follow‐up duration was 110 days (range, 14‐840). A total of 102 (88%) patients had their driver mutation tested of which 59 (58%) were epidermal growth factor receptor (EGFR) mutants. Factors predicting for better survival were female gender ( P  < .001), EGFR mutant receiving TKIs ( P  = .013), prescription other than 20 Gray in five fractions ( P  = .003), and presence of more than four BM ( P  = .001). Conclusion: Our patients appear to be considerably different from those recruited into the QUARTZ trial. Further prospective studies should be done to evaluate the value of WBRT in our population.